2021
DOI: 10.1007/s10592-021-01394-7
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq reveals adaptive genetic potential of the rare Torrey pine (Pinus torreyana) in the face of Ips bark beetle outbreaks

Abstract: The ability of tree species to adapt to water stress and increased frequency of bark beetle outbreaks with climate change may increase with population size and standing genetic variation, calling into question the resilience of small, rare plant populations. The Torrey pine (Pinus torreyana) is a rare, genetically depauperate conifer that occurs naturally in a mainland and island population in southern California. Due to recent declines in the mainland population coinciding with drought and Ips paraconfusus ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…A paleoecological study revealed that the population of the pine was exceedingly small historically. Consequently, the genetic diversity of the pine is very low (Ledig and Conkle 1983;Whittall et al 2010;Steele et al 2021). Spatial distributions of the stand structure and recruitment pattern of the pine have been studied (Wells and Getis, 1999;Franklin and Santos 2011), and more recent efforts have investigated the evolutionary potential of the pine (Hamilton et al 2017;Steele et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A paleoecological study revealed that the population of the pine was exceedingly small historically. Consequently, the genetic diversity of the pine is very low (Ledig and Conkle 1983;Whittall et al 2010;Steele et al 2021). Spatial distributions of the stand structure and recruitment pattern of the pine have been studied (Wells and Getis, 1999;Franklin and Santos 2011), and more recent efforts have investigated the evolutionary potential of the pine (Hamilton et al 2017;Steele et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Given historical and contemporary estimates of effective population size as well as contemporary estimates of expected heterozygosity, our results indicate Torrey pine may not retain the genetic variation within populations needed to adapt to change. Current monitoring within the mainland population suggests a lack of recruitment (personal observation by Lionel Di Santo, July 2017), infestation by Ips beetles (Steele et al, 2021), and climate warming (Diffenbaugh et al, 2015) may increase extinction risk. Thus, for Torrey pine, increased Ne and greater genetic diversity may be required for long-term persistence.…”
Section: Applying Neutral and Adaptive Evolutionary Processes To Rare...mentioning
confidence: 99%